(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This study evaluates the biological activity and possible deterrance played by organic crude extracts from six Phaeophyta and two Rhodophyta algae from Southern Caribbean. Bioessays were carried out using concentrations equivalent to those present in algae tissue. Species in general did not show high citotoxic activity. However Dictyota pulchella, showed a delay in the mitotic process for cells stage XVI. Extracts from Dictyota bartayresiana, D. pulchella, Sargassum cymosum and Cladophyllum schnetteri, inhibited S. partitus feeding under laboratory conditions. Nontheless, only extracts from D. bartayresiana and C. schnetteri showed this activity in the field.